2021
DOI: 10.1108/lodj-07-2020-0307
|View full text |Cite
|
Sign up to set email alerts
|

When to challenge employees' comfort zones? The interplay between culture fit, innovation culture and supervisors' intellectual stimulation

Abstract: PurposeThis study, first, examines whether a low culture person–organization (P-O) fit reduces job satisfaction and organizational citizenship behavior (OCB). Second, the author investigates how an organization's current innovation culture affects employees' attitudes and behaviors. Third, the author focuses on the interplay between leadership and organizational culture by testing whether supervisors' intellectual stimulation can mitigate the negative effects of a low innovation culture.Design/methodology/appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Yuwono et al (2023) found that this benefits all organizational activities. However, poor organizational culture lowers job satisfaction and OCB rates (Endrejat, 2021;Habeeb, 2019).…”
Section: Hypothesis-research Design Relationshipmentioning
confidence: 99%
“…Yuwono et al (2023) found that this benefits all organizational activities. However, poor organizational culture lowers job satisfaction and OCB rates (Endrejat, 2021;Habeeb, 2019).…”
Section: Hypothesis-research Design Relationshipmentioning
confidence: 99%
“…Innovation performance, on the other hand, is a comprehensive reflection of the results of technological innovation in an organization (Endrejat, 2021). From the perspective of process, it identifies the behavioral process by which the members of the firm grow continuously through the process of acquiring and sharing knowledge (Cao, 2021).…”
Section: Organizational Performancementioning
confidence: 99%
“…Thriving at work is a psychological state of an employee and obtained through learning and by experiencing vigor at work. Learning refers to the enhancement of self-confidence and strength through knowledge and skills, and vigor represents employees’ high level of energy at work ( Amabile, 1988 ; Spreitzer et al, 2005 ; Endrejat, 2021 ). Empowering leadership can help employees build confidence, encourage them to try new methods and promote continuous learning ( Fry et al, 2005 ; Hirak et al, 2012 ; Meng, 2016 ).…”
Section: Research Modelmentioning
confidence: 99%